ANALYSIS OF PUBLIC SECTOR INVOLVEMENT IN LOCAL ECONOMIC EMPOWERMENT AS IMPLEMENTATION OF MICRO AND SMALL ENTERPRISE DEVELOPMENT POLICIES - Golam, Mohamad Yusuf; Akhtari, Mitra; Lasmiatun , KMT (Multifinance, 2024)
The purpose of this study is to examine the public sector's involvement in local empowerment economies as well as the implementation of policies for micro and small businesses. The research method used is qualitative research. Qualitative research is a research method used to understand social phenomena in depth. This type of research is literature study research, which researchers carry out by collecting, studying, and analyzing references or sources obtained in written or written form, such as books, journals, articles, documents, and other sources of information that are significant to the topic or title being researched. The study's findings show that empowering the local economy, particularly through support for micro and small businesses (UMK), plays a critical role in increasing economic growth and sustainable development in Indonesia. MSEs don't only become a bone-back economy locally by creating fieldwork and contributing to domestic income, but they also strengthen the resilience economy area to change the global economy. Apart from that, MSEs also play a role in strengthening identity culture and the local sustainability environment with produce-rooted goods and services in inheritance culture and local traditions. Empowering the local economy through support for MSEs involves not only increasing access to sources of power but also empowering the public to play a role in their development.